BANGKITAN PERJALANAN BERDASARKAN JENIS PENDIDIKAN DAN PEKERJAAN DI KECAMATAN MUTIARA KABUPATEN PIDIE - Nurmiswari Nurmiswari; Renni Anggraini; Sugiarto Sugiarto (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2020)
The Mutiara Sub-district to date has continued to experience a relatively rapid population growth rate, limited existing road network facilities, and increased development in urban centers that are not well organized. This phenomenon will burden and will adversely affect the city transportation system because it will cause the occurrence of transportation problems such as queues, or traffic congestion in certain areas. Therefore, it needs a model of the movement generation in the Mutiara Sub-district. This study aims to determine the pattern of the rise of household movements, based on the type of education and occupation reviewed in mandatory and non-mandatory activities in Kecamatan Mutiara. The population in Mutiara sub-district is 20,810 people, through the Slovin formula, the sample is 393 people. The sampling technique used is proportionate stratified random sampling. Calibration of regression parameters used Ordinary Least Square (OLS) method with Statistical Product and Service Solution (SPSS) version 22 software. The results showed that the mandatory activity of the upward movement of high school education was influenced by sex factors, the number of family members who were still in school, and the ownership of the driver's license, the rise of the movement of the trader's work is influenced by sex factors, and the number of family members already employed, and the rise of non-trades work movements is influenced by the number of family members who are still in school, the number of cars in the family, and the ownership of the driver's license. In non-mandatory activities, the rise of the high school education movement is influenced by the number of family members in school, the number of cars, and the ownership of the driver's license.